Elasticity at the Canada–US border: Jurisdiction, rights, accountability. (May 2019) - Gilbert, Emily
Borders are being stretched as they are deterritorialized, reterritorialized and extra-territorialized. But borders are not only being relocated elsewhere: just as they are extended they are also snapped back into place in order to limit the rights of travellers and migrants, and to deny the accountability of border officials. This elasticity—expansion but also contraction—is the focus of this paper, with particular attention to the Canada–US border with respect to how legal jurisdiction is being reworked territorially, and the ways that the law gets attached to particular bodies. Three contemporary case studies are examined: the Safe Third Country Agreement, the Shiprider program, and the expansion of preclearance programs. While each of these cases is quite different in that they deal with asylum seekers, cross-border policing, and extra-territorial customs programs, together they illustrate how borders are being made elastic, and with what political implications.